Cooperatives as Entities Influencing the Sustainable Development of Rural Areas in European Union - Suchoń, Aneta (Indonesian Comparative Law Review, 2022)
The aim of the article was, first of all, to determine whether and to what extent legal regulations favour cooperatives and influence the development of rural areas in Poland and selected countries of Western Europe. Secondly, it attempts to indicate the possible directions for the development of cooperatives in rural areas in light of the new rules of the Common Agricultural Policy after 2022 and the European Green Deal. The basic research method involved the dogmatic analysis of normative texts, which is a characteristic feature of a lawyer’s work. At the beginning of the article selected issues related to cooperatives in the European Union and EU rural development principles were presented, then regulations concerning the establishment and operation of cooperatives in Poland, Germany, France and Italy. The next part of the article refers to the new EU regulation of December 2021, which will enter into force on 1 January 2023; and indicate regulations that will be of benefit to cooperatives and that will particularly contribute to the development of rural areas. The issue of the European Green Deal and its impact on association in the form of cooperatives was also discussed.